ISIS, GENOCIDE AND A â€œTHICK DESCRIPTIONâ€ OF POWER - Nazala, Rochdi Mohan (Department of International Relations, Brawijaya University, 2019)
IntroductionOn August 3, 2015, Islamic State in Iraq and Syria (ISIS) fighters were marching with full military equipment to Kocho, a village that belongs to Yazidi, one of the minorities in Iraq, near Mount Sinjar (Kikoler, 2015). They captured 1200 men, women and children whom in the next two days ISIS told to leave their religious practice, which is a combination of elements of Zoroastrianism, Judaism, Christianity, and Islam and to convert to Islam. When the majority of Yazidi's men refused the demand, all of them were taken with their eyes blindfolded around 500 meters outside the village, and upon arriving at the destination, they were lined up, videotaped and shot (Amnesty International Canada, August 18, 2014). The women became sex slaves (Smith, 2014) and the children were transferred to ISISâ€™s camp to train as soldiers (McLaughlin, 2016).The story above from Kocho is a one of frames that is used repeatedly to justify the allegation of ISIS conducting genocide toward Yazidi as well as other minorities in Iraq and Syria. The European Union, for instance, announced in the beginning of 2016 that ISIS was